Evidence-based review in the field of developing critical appraisal tools for quantitative studies - Mehrnaz Ahmadi; Ladan Sedighie; Camelia Rohani (Kurdistan University of Medical Sciences, 2018)
Background & Aim: Selection of an appropriate critical appraisal tool is an important part of evidence-based practice. The aim of the present study was to do a systematic review of articles according to existing evidence in databases in the field of developing critical appraisal tools for quantitative studies from 2006 to 2016. Materials & Methods: A systematic review was performed on the critical appraisal tools for quantitative studies between 8 to 12 January 2016 in the PubMed, ProQuest, Ovid, Web of Science, Scopus and Cochrane databases using keywords in the MeSH and based on inclusion and exclusion criteria. Results: Of the 1100 retrieved articles, 19 articles were only remained in the study. Workshop, Delphi technique, a panel of experts and exploration method have been used for development of the critical appraisal tools for observational studies (STROBE, STROBE-NI, RECORD, STROME-ID, STROBE-nut AXIS, STROBE-ME, CORE), clinical trials studies (CONSORT and different types, STRICTA, SPIRIT, CA of RCTs of NPs), interventional studies (QI-MQCS), case studies (CARE and SCARE). Also, a general assessment tool (CAT) and a special tool for assessment of the psychometric characteristics of the studies (COSMIN) were presented. Conclusion: A number of useful critical appraisal tools have been identified in this review; however, the validity and reliability of the tools did not show enough attention in these studies. Researchers and referees should be aware of the selection of a simple, valid and reliable critical appraisal tool during the writing of the quantitative articles or evaluation of them can be a useful guide.